Are Depressive Symptomatology, Self‐Efficacy, and Perceived Social Support Related to Disability and Quality of Life in Patients With Chronic Migraine Associated to Medication Overuse? Data From a Cross‐Sectional Study. Issue 5 (23rd April 2015) - D'Amico, Domenico; Grazzi, Licia; Bussone, Gennaro; Curone, Marcella; Di Fiore, Paola; Usai, Susanna; Leonardi, Matilde; Giovannetti, Ambra Mara; Schiavolin, Silvia; Raggi, Alberto
<x xml:space="preserve">Abstract</x> Background Chronic migraine with medication overuse (CM‐MO) impairs quality of life (QoL) and causes disability. Psychosocial variables such as depressive symptomatology, self‐efficacy, and social support have been sparingly investigated, and their impact on disability and QoL is unknown. Methods Patients with CM‐MO under withdrawal were consecutively enrolled. Standardized measures of disability and QoL were used as outcomes; psychosocial (ie, mood state, self‐efficacy, social support) and clinical (ie, headache frequency and intensity) variables were considered as associated variables. Associations between these variables, disability, and QoL were tested with Pearson's correlations. Hierarchical multiple regression was used to assess the cumulative contribution of psychosocial variables on disability and QoL variation when added to clinical variables. Results One hundred ninety‐four patients were enrolled; 82.5% were females and mean age was 43.9. Disability and QoL were moderately or little correlated to clinical and psychosocial variables. Models based on clinical variables explained 7.5‐14.3% of disability and QoL variation, with pain intensity being the only significant predictor; when psychosocial variables were added, the explained variation increased to 21.5‐35.2%, with depressive symptomatology always having independent predictive power and perceived social support having independent predictive power in the regression model over role‐prevention component of QoL. Conclusions Adding information on psychosocial variables to headache features improved our ability to understand disability and QoL of CM‐MO patients. We deem that the inclusion of psychosocial variables in standard evaluation protocols may contribute to the global assessment of CM‐MO patients, and eventually to their success in reducing the personal and social impact of this condition. Future longitudinal studies are needed to confirm this hypothesis.